Antimicrobial activity of Calendula officinalis, Camellia sinensis and chlorhexidine against the adherence of microorganisms to sutures after extraction of unerupted third molars - Faria, Raquel Lourdes; Lourenco Cardoso, Lincoln Marcelo; Akisue, Gokithi; Pereira, Cristiane Aparecida; Junqueira, Juliana Campos [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP]; Santos Junior, Paulo Villela [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2011)
Objective: The objective of this study was to compare the antimicrobial effect of mouthwashes containing Calendula officinalis L., Camellia sinensis (L.) Kuntze and 0.12% chlorhexidine digluconate on the adherence of microorganisms to suture materials after extraction of unerupted third molars. Material and Methods: Eighteen patients with unerupted maxillary third molars indicated for extraction were selected (n=6 per mouthwash). First, the patients were subjected to extraction of the left tooth and instructed not to use any type of antiseptic solution at the site of surgery (control group). After 15 days, the right tooth was extracted and the patients were instructed to use the Calendula officinalis, Camellia sinensis or chlorhexidine mouthwash during 1 week (experimental group). For each surgery, the sutures were removed on postoperative day 7 and placed in sterile phosphate-buffered saline. Next, serial dilutions were prepared and seeded onto different culture media for the growth of the following microorganisms: blood agar for total microorganism growth; Mitis Salivarius bacitracin sucrose agar for mutans group streptococci; mannitol agar for Staphylococcus spp.; MacConkey agar for enterobacteria and Pseudomonas spp., and Sabouraud dextrose agar containing chloramphenicol for Candida spp. The plates were incubated during 24-48 h at 37 degrees C for microorganism count (CFU/nnL). Results: The three mouthwashes tested reduced the number of microorganisms adhered to the sutures compared to the control group. However, significant differences between the control and experimental groups were only observed for the mouthwash containing 0.12% chlorhexidine digluconate. Conclusions: Calendula officinalis L. and Camellia sinensis (L.) Kuntze presented antimicrobial activity against the adherence of microorganisms to sutures but were not as efficient as chlorhexidine digluconate.
Keywords: Calendula officinalis L.; Camellia sinensis (L.) Kuntze; Chlorhexidine; Antimicrobial activity